Trends in incidence and mortality of melanoma skin cancer in the city of Aracaju in the last 20 years (Research, Society and Development, 2022)
Skin cancers are the most common neoplasms in the world. Among them, melanoma accounts for about 5% of all skin cancers and ¾ of all deaths in this group. Neoplasms are the second leading cause of death in Brazil, but it has a good prognosis when diagnosed early. This study aims to analyze the temporal evolution of the incidence and mortality of Melanoma Skin Cancer in the city of Aracaju in the last 20 years, according to sex and age group, through the Aracaju Cancer Registry, analyzed by the near-likelihood model through the software R Core Team 2022 (Version 4.2.1). We observed different behaviors in relation to the incidence rate, with an increase in cases in Aracaju from 1996 to 2008, which suggests an increase in the number of notifications in this period, while in subsequent years there was a stagnation of the growth curve, both sexes. CPM is more common in young women, due to intentional sunlight exposure and the search for dermatological care. In the mortality rate, we observed the increase in the number of cases from 1996 to 2006 and constant until 2021 and higher in men, probably due to the late search for treatment, greater exposure to risk factors and poor adherence to solar protection. Thus, we highlight the importance of prevention through population education by qualified health professionals, for the identification, notification and early intervention of cases.